Unlocking the potential of cacao bean shell as a functional food additive: composition, applications, optimization, and future directions – a review - Sanchez, Philip Donald C.; Hashim, Norhashila; Mohd Basri, Mohd Salahuddin; Saari, Nazamid; Muhammad, Dimas Rahadian Aji (Elsevier, 2025)
Cacao bean shell (CBS) has garnered increasing attention in recent years due to its functional properties, which closely resemble those of cacao beans, the primary ingredient in chocolate production, offering potential health benefits. However, despite its recognition and promising applications as a functional ingredient, research on its optimization for food formulations remains limited. While studies have highlighted its rich polyphenol content, methylxanthine composition, and antioxidant properties, there is a lack of sufficient data on the application of Response Surface Methodology (RSM) to optimize the extraction and incorporation of these compounds into dough-based products. Furthermore, the impact of CBS on the functional, sensory, and rheological properties of dough formulations remains underexplored, posing challenges for large-scale food applications. This review aims to address these gaps by discussing current findings, investigating RSM-based optimization strategies, and identifying future research directions to enhance the industrial feasibility of CBS as a sustainable functional additive for food and bakery products.